DETERMINANTS OF HEALTH SERVICE UTILIZATION IN LOW-INCOME FAMILIES IN THE COASTAL REGION OF MAGINTI ISLAND, WEST MUNA REGENCY: A CROSS-SECTIONAL STUDY: HEALTH SERVICE UTILIZATION IN LOW-INCOME FAMILIES - Saltar, Laode; Risaldi, Adi; Kadarman, Achmad; Heltty (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Accessibility to healthcare services remains a significant challenge among low-income families in coastal regions such as Maginti Island, West Muna Regency. Several socioeconomic and environmental factors are believed to influence the utilization of available health services. This study aimed to identify the factors associated with the utilization of healthcare services among poor families in Maginti Island. Methods: A quantitative, cross-sectional study was conducted from May to July 2024. A total of 57 respondents were selected using simple random sampling. Data were collected using structured questionnaires and analyzed using univariate and bivariate methods (Chi-square test). Results: The study found significant associations between healthcare service utilization and three main factors: knowledge of health, availability of transportation, and household income level (p < 0.05). Families with better knowledge, easier access to transportation, and higher income levels were more likely to use healthcare services. Conclusion: Socioeconomic status, transportation access, and knowledge play crucial roles in determining healthcare utilization among the poor in Maginti Island. Strengthening health education and infrastructure is essential to improving healthcare access in coastal communities.